Prediction of Direct Runoff from a Hilly Watershed without Using Past Data of Rainfall and Runoff - Kumar, Anil; Kumar, Devendra (Journal of Agricultural Engineering, 2004)
A geomorphologic instantaneous unit hydrograph (GIUH) model, based on kinematic-wave and stream order ratios, has been developed to predict the direct runoff hydrograph from a hilly sub-watershed of Ramganga river catchment in Uttaranchal (India). The travel times for overland and stream flows in a stream-ordering system of the watershed have been determined analytically and probabilistically to derive the GIUH, without using the past record of rainfall and runoff data. The performance evaluation of the developed model indicates that the predicted and observed direct runoff hydrographs for the stom, events occurring in the watershed are in good correlation. Since the development of this model utilizes only the geomorphological parameters of the watershed, this model is very well applicable to any ungauged hilly watershed.